(untitled) (Eurasian Medical Research Periodical, 2022)
The study of pharmacogenetic aspects of pharmacoresident epileptic patients is very little studied in medicine. To study the pharmacokinetics of convulex using therapeutic drug monitoring and pharmacogenetic testing to optimize the treatment of patients with epilepsy